Do Your MBA Programme Online - The, Star (The Star, 2019)
Asia e University (AeU) online Master of Business Adminstration (MBA) programme is innovatively designed to enrich the skills of professionals who desire to step out of their comfort zone to upgrade their knowledge in the comprehensive aspects of management and business, whether to enhance or make a change in their careers.